2019
DOI: 10.1186/s13287-019-1250-9
|View full text |Cite
|
Sign up to set email alerts
|

Xenotransplantation of canine spermatogonial stem cells (cSSCs) regulated by FSH promotes spermatogenesis in infertile mice

Abstract: Background Xenotransplantation of spermatogonial stem cells (SSCs) has become a popular topic in various research fields because manipulating these cells can provide insights into the mechanisms associated with germ cell lines and the entire spermatogenesis process; moreover, these cells can be used in several biotechnology applications. To achieve successful xenotransplantation, the in vitro microenvironment in which SSCs are cultured should be an ideal microenvironment for self-renewal and simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…To overcome the obstacle for reestablishing complete spermatogenesis in adult individuals, a recent study demonstrated the possibility of inducing infertility in mice and then injecting spermatogonia cells derived from dogs into mouse testes, where it was possible to verify the repopulation capacity of germ cells. 57 This study shows an alternative for the use of samples from domestic and wild adult animals that have not yet succeeded in the xenotransplantation of testicular fragments.…”
Section: Grafting and In Vitro Culture Of Testicular Tissuesmentioning
confidence: 95%
“…To overcome the obstacle for reestablishing complete spermatogenesis in adult individuals, a recent study demonstrated the possibility of inducing infertility in mice and then injecting spermatogonia cells derived from dogs into mouse testes, where it was possible to verify the repopulation capacity of germ cells. 57 This study shows an alternative for the use of samples from domestic and wild adult animals that have not yet succeeded in the xenotransplantation of testicular fragments.…”
Section: Grafting and In Vitro Culture Of Testicular Tissuesmentioning
confidence: 95%
“…Rodents can complete spermatogenesis without FSH stimulation, but its deficiency significantly decreases sperm quantity. Xenotransplantation of canine spermatogonial stem cells (SSCs) into mice testicular tissues was found to promote spermatogenesis in infertile mice when regulated by FSH [ 162 ].…”
Section: Fsh In the Adult Phase: Folliculogenesis And Spermatogenesismentioning
confidence: 99%
“…When cSSCs were transplanted in chemoablated mouse testes, cSSCs were found in seminiferous tubules. We discussed this paracrine effect of FSH as being possible via Sertoli cells, which express FSHR and secrete more GDNF in the presence of FSH, resulting in increased numbers of SSCs [ 162 ]. Other in vitro studies with bovine and mouse SSCs demonstrated the influence of FSH in the self-renewal and proliferation processes mediated by GDNF and FGF2 [ 237 ], confirmed by the expression of GFRα1 [ 238 , 239 ].…”
Section: Influence Of Fsh On Germ Cellsmentioning
confidence: 99%
“…NOA was quilt different form obstructive azoospermia which presents with obvious testis microstructure changes. NOA is a result of meiotic arrest, and it has been suggested that microenvironment changes may play critical roles [22] . Therefore, it is important to understand the biological characteristics of testis, and explore the gene expression status and identity of NOA-associated genes.…”
Section: Discussionmentioning
confidence: 99%